Analisis Kebijakan Penertiban Bangunan di Atas Drainase Berdasarkan Peraturan Wali Kota Medan Nomor 9 Tahun 2009 Dalam Perspektif Fiqih Siyasah - Barus, M. Hafiz Ramdhani; Marpaung, Zaid Alfauza (SENTRI: Jurnal Riset Ilmiah, 2025)
This study analyzes the implementation of Medan Mayor Regulation Number 9 of 2009 concerning the prohibition of constructing buildings over drainage systems, examined through the lens of fiqh siyasah (Islamic political jurisprudence). The research focuses on the policy’s effectiveness in Medan Helvetia District and explores the extent to which fiqh siyasah principles provide normative and ethical justification for the regulation. Utilizing a juridical empirical legal approach combined with a socio-juridical method, the study reveals that the regulation’s enforcement faces significant challenges, including low public legal awareness, economic pressures, and inconsistent law enforcement. From an Islamic jurisprudential perspective, the policy aligns with the principles of maslahah (public interest) and maqāṣid al-sharī‘ah (objectives of Islamic law). However, its execution must incorporate justice, consultation (shūrā), and community education. The study recommends integrating positive law with Islamic ethical values to promote equitable, sustainable, and socially legitimate urban spatial governance.